Formas, processos e materiais: uma proposta de evolução geomorfológica multiescalar da borda meridional do carste de Lagoa Santa, em Vespasiano, Minas Gerais - Renata Jordan Henriques (2017)
The earth's surface is the object of investigation in Geomorphology through attempts to understand the relief forms, their materials and the processes that sculpure them along multiple spatio-temporal scales. This research was structured from observations about the surface coverings located in the transition between two different geotectonic units in Minas Gerais, that is, the sedimentary basin of the Bambuí Group that structures the karst of Lagoa Santa and the crystalline exhumed shield of Belo Horizonte. The spatial distribution of this work corresponds the area of the Sujo stream basin located in the municipality of Vespasiano, about 15km north of the capital Belo Horizonte. This stream is a tributary of the Da Mata stream, which, in turn, flows to the river of the Velhas. The main question guiding this research is: what is the geomorphological significance of the recurrence of concentrations of coarse fragments of subround and subangulars quartz found in the unconsolidated covers in the domain of this drainage basin? For this response, the methodological procedures involved fieldwork, cabinet, laboratory and geoprocessing to help interpret and assign meanings for these materials. The development of this research still used the multiple scales of approach that have shifted from regional to local perspectives, especially in the analysis of other components such as the hydrographic network and the geological framework that provide coherent answers on the superficial coverages. The interpretations on the data produced by these various procedures concluded that these coverings have allochthonous affiliations which bear testimonies of different moments in the history of morphogenetic evolution of the investigated area. Therefore, two model proposals were formulated that reconstitute an evolutionary past that structured the investigated materials. The first model reflects a relatively regional approach and involves the structuring of the current perimeter of the dirty stream basin and the evolutionary path of its surface coverings. The second model, on the other hand, deals with the genesis and evolution of materials that make up the single representative section of these covers and their thick fragments of quartz, that is, it involves a relatively local scalar perspective. Although the scales are different, the results of both models reflect relative coherence between the phenomena addressed, although they had different approaches in the scale of investigation. Notably, the models indicated that there were different morphodynamic energy balances, being conditioned by different base levels, intercontinental crustal readjustments and hydrological reorganizations, which in turn interfered with the way relief forms were modeled and their surface coverings were structured.